Pembaharuan Isu Perpajakan pada Mahasiswa Universitas Widya Dharma Pontianak - Lauw Sun Hiong; Hengky Leon; Dedi Haryadi; Ricky Ricky (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Maintain economic stability and meet the needs of the community, tax revenue is one of the vital sources of revenue for the government. However, major challenges often arise in ensuring that all taxpayers meet their tax obligations correctly. Tax is a compulsory contribution to the state that must be paid by an individual or entity, which is coercive in accordance with the provisions of the law, without getting direct compensation, used in order to meet the needs of the state in order to achieve maximum welfare of the people. Payment of taxes to the state is mandatory for taxpayers, both individuals and entities. Tax payment is a form of community cooperation in national financing and development, which aims primarily to improve the welfare and prosperity of the entire community. The target of this community service activity is Widya Dharma University Pontianak students who have registered. This activity is held based on needs and increases students' knowledge and abilities by providing socialization. After the socialization was delivered, students understood and realized the importance of accurate and responsible reporting as taxpayers. Follow-up efforts include re-examination of annual tax returns, awareness raising, conducting further consultation processes, participation in voluntary disclosures and reminders and further counseling.